# Simplify `(root(3)(sqrt(a^3+b^2)+b)))*(root(3)(sqrt(a^3+b^2)-b))`

### 1 Answer | Add Yours

Simplify `root(3)(sqrt(a^3+b^2)+b)*root(3)(sqrt(a^3+b^2)-b)`

First use `root(3)(m)*root(3)(n)=root(3)(mn)` to rewrite as:

`=root(3)((sqrt(a^3+b^2)+b)(sqrt(a^3+b^2)-b))`

Now multiply the binomial -- recall that `sqrt(m)sqrt(m)=m`; also note that this is the difference of two squares :

`=root(3)(a^3+b^2-b^2)`

`=root(3)(a^3)`

`=a`

----------------------------------------------------------------

`root(3)(sqrt(a^3+b^2)+b)*root(3)(sqrt(a^3+b^2)-b)=a`

---------------------------------------------------------------